3D atlas of the human fetal chondrocranium in the middle trimester - Kaiser, Markéta; Zikmund, Tomáš; Vora, Siddharth; Metscher, Brian; Adameyko, Igor; Richman, Joy M; Kaiser, Jozef (Scientific data, 2024)
The chondrocranium provides the key initial support for the fetal brain, jaws and cranial sensory organs in all vertebrates. The patterns of shaping and growth of the chondrocranium set up species-specific development of the entire craniofacial complex. The 3D development of chondrocranium have been studied primarily in animal model organisms, such as mice or zebrafish. In comparison, very little is known about the full 3D human chondrocranium, except from drawings made by anatomists many decades ago. The knowledge of human-specific aspects of chondrocranial development are essential for understanding congenital craniofacial defects and human evolution. Here advanced microCT scanning was used that includes contrast enhancement to generate the first 3D atlas of the human fetal chondrocranium during the middle trimester (13 to 19 weeks). In addition, since cartilage and bone are both visible with the techniques used, the endochondral ossification of cranial base was mapped since this region is so critical for brain and jaw growth. The human 3D models are published as a scientific resource for human development.
Keywords: Imaging, Three-Dimensional; Skull; X-Ray Microtomography; Fetus; Female; zobrazování trojrozměrné; plod; Pregnancy; rentgenová mikrotomografie; ženské pohlaví; lebka; Humans; lidé; chrupavka; těhotenství; Cartilage